UJI ANTIMIKROBA BAWANG BATAK (Allium chinense G. Don.)TERHADAP DIAMETER ZONA HAMBAT BAKTERI Escherichia coli dan Salmonella typhi - Dini Julia Sari Siregar; Ma’aruf Tafsin; Warisman Warisman (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Prevention of poultry diseases caused by Escherichia coli and Salmonella typhi contamination such as diarrhea, usually poulterers use antibiotics, but the use of antibiotics in the ration has become controversial because it causes residues that can endanger consumers. Alternative potential substitutes for replacing the function of antibiotics are herbal plant / plant extracts that contain active plant compounds and some antioxidant, antimicrobial and immunostimulant compounds. One of the plants that can be used as an anti-microbial which is especially a local variety plant in Indonesia, especially North Sumatera, is Allium chinense G.Don is called “Bawang Batak”. Therefore, it is widely used as an antimicrobial and antifungal. Specific research topic is evaluating the antimicrobial activity of the onion extract against the inhibitory growth of pathogenic bacteria (Escherichia coli and Salmonella typhi) with several solvents and concentrations. The aim of this study was to determine the diameter of inhibitory zones of pathogenic bacteria, including Escherichia coli and Salmonella typhi with the effect of giving concentrations of batak onion extract (12.5%, 25%, 50% and 75%) and solvents of ethyl acetate, 70% ethanol and methanol. This research was carried out by the preparation of Bawang Batak Extract (Allium cinense G.Don) and the technique of data collection was Inhibition of Zone Diameter through in vitro tests. The results showed that the best treatment of interaction combination was 75% of  Bawang Batak extract with ethyl acetate treatment as an inhibitory zone against Escherichia coli bacteria, which was 20.83 mm and Salmonella typhi 20.73 mm. Based on the calculation of the polynomial equation, the more of the concentration percentage of the bawang batak  of extract with the ethyl acetate solvent added, the greater the diameter of the Escherichia coli inhibitory zone.